Synthesis and electrochemical properties of porous CNTs-ferrite hybrid nanostructures for supercapacitor - Tam, Le T. T.; Hung, Nguyen V.; Tung, Doan T.; Dung, Ngo T.; Dung, Hoang T.; Dung, Nguyen T.; Minh, Phan N.; Hong, Phan N.; Lu, Le T. (Vietnam Journal of Science and Technology, 2019)
Carbon nanotubes (CNTs)-ferrites hybrid nanomaterials have attracted extensive research interest owing to their large specific surfae area, high electrical, thermal conductiviy and outstanding electrochemical properties, which are widely investigated for energy conversion and storage devices. Regular syntheses rely mainly on the in situ growth of ferrite nanoparticles (NPs) in the presence of the preformed CNTs. It is very challenging to control the composition and morphology of the individual components, and to scale-up the synthesis. In this work, ferrite NPs were prepared by solvothermal method. Porous (3D) CNTs-ferrites hybrid aerogels were fabricated by using freeze gelation method. The results indicate that the obtained 3D CNTs-ferrites aerogels were very porous, highly electrical conductive and have good electrochemical properties.